Physico-Chemical Properties Of Starch In Sago Palm (Metroxylon Sagu) At Different Growth Stages - Tie, Adrina Pei Lang (2004)

(untitled)
This study aimed to characterise the physico-chemical properties of sago starch from base and mid heights of palms at different growth stages